A Person-Centered Approach to Cardiovascular Genetic Testing - Platt, Julia (Cold Spring Harb Perspect Med, 2020)
Cardiovascular genetic counselors provide guidance to people facing the reality or prospect of inherited cardiovascular conditions. Key activities in this role include discussing clinical cardiac screening for at-risk family members and offering genetic testing. Psychological factors often influence whether patients choose to have genetic testing and how they understand and communicate the results to at-risk relatives, so psychological counseling increases the impact of genetic education and medical recommendations. This work reviews the literature on the factors that influence patient decisions about cardiovascular genetic testing and the psychological impact of results on people who opt to test. It also models use of a psychological framework to apply themes from the literature to routine cardiovascular genetic counseling practice. Modifications of the framework are provided to show how it can be adapted to serve the needs of both new and experienced genetic counselors.